Comparison of Effectiveness of Induction of Labour between Misoprostol Per Oral and Per Vaginal - Sara Gul, Tabassum Ali, Amber Bashir, Asma Ali, Maryam Bibi, Asia Asghar (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Oral misoprostol as a labor inducing agent (IOL) is quickly attaining popularity under resource constraints due to its cheapness, stability at room temperature, and logistically easier administration in comparison to oxytocin and dinoprostone. We purpose to inspect the effectiveness and safety of a regimen of oral misoprostol in in the Gynae/Obs unit at Rehman Medical Institute, Peshawar Pakistan. Material and Methods: This was Randomized Controlled Trial conducted at department of Gynecology & Obstetrics, Rehman Medical Institute, Hayatabad, Peshawar, from December, 2016 to May, 2017.In this study a total of 200 (100 in each group) patients were observed. After the drug administration, per vaginal examination was done at 4 hourly intervals to see for labor induction/pains. Data was collected by means of proforma. Results: In this study, the mean age was 31.2 with SD ± 3.51 in group B and the mean age was 32.80 with SD ± 4.02 in Group A. Oral route (Misoprostol, 50μg) (Group A) was operative in 80% patients and was not effective in 20% patients. While Vaginal route (Misoprostol, 25μg) (Group B) was effective in 88% patients and was not effective in 12% patients. Conclusion: The oral misoprostol IOL regimen designated in this analysis is effective, safe and logistically practicable to direct with limited resources.